Compostos 1,2 e 1,4-dicarboxílicos atuam sobre o sistema glutamatérgico e o comportamento de ratos e camundongos - Sinhorin, Valeria Dornelles Gindri (2005)
Glutamatergic receptors are targets for many L-glutamate structure analogues, which cause neurotoxicity. This study investigated the actions of two dicarboxylic compounds, the first had cyclic framework and rigid structure, and the other had an acyclic framework and flexible structure, on the glutamatergic neurotransmission, oxidative damage and behavior in mice. The first compound evaluated was D,L-cis-2,3-pyrrolidine dicarboxylate (D,L-cis-2,3-PDC), a new glutamate analogue. D,L-cis-2,3-PDC reduced sodium-independent [3H]-L-glutamate binding by 50% in lysed membrane preparations and had no effect on sodium-dependent glutamate binding. Intracerebroventricular administration (ICV) of D,L-cis-2,3-PDC (7.5 - 25 nmol/ 5μl) induced dose-dependent tonic-clonic convulsions. The co-administration of MK-801 (7 nmol/ 2.5 μl; ICV), a noncompetitive NMDA receptor antagonist, with D,L-cis-2,3-PDC (16.5 nmol/ 2.5 μl; ICV) fully protected the animals against D,L-cis-2,3-PDC-induced convulsions, while the co-administration of DNQX (10 nmol/ 2.5 μl; ICV), a AMPA and KA receptors antagonist, increased the latency to convulsion and did not alter the percentage of animals that had convulsions. These results suggest that D,L-cis-2,3-PDC-induced effects are mediated predominantly by NMDA receptors activation. The second compound studied was succinate, the accumulating substrate in succinate dehydrogenase (SDH) deficiencies and SDH inhibitor intoxication. Adult male mice received an ICV injection of succinate (0.7, 1.0 and 1.7 μmol/ 5 μl) or 0.9% NaCl (5 μl) and had their exploratory behavior assessed in an open field for 10 min. Succinate (0.7 and 1.0 μmol/ 5 μl) decreased locomotor activity behavior and increased thiobarbituric acid reactive substances (TBARS) and protein carbonylation in the forebrain. Conversely, 1.7 μmol of succinate did not alter locomotor activity or oxidative damage parameters. The involvement of NMDA receptors in the succinate-induced increase of total protein carbonylation content and exploratory behavior inhibition was assessed by co-administrating MK-801 (7 nmol/ 2.5 μl, ICV) with succinate (1 μmol/ 2.5 μl, ICV). The co-administration of MK-801 protected against succinate-induced increase of total protein carbonylation and decrease of locomotor activity. These results suggest the involvement of NMDA receptors in these effects of succinate, which may of particular relevance for succinate-accumulating conditions, such as SDH inhibitors intoxication and inherited SDH deficiencies.